Meningkatkan Pemahaman Materi Profesi dalam Pembelajaran IPS Lanjut melalui Metode Bermain Peran pada Kelas IV di MI Darul Ma’arif Numbay - Diva Amilia Ramadhani; Alma Pratiwi Husain (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
By using the role-playing method, the knowledge of professions in this learning aims to improve students' understanding of the material on professions in the Social Studies (IPS) subject for fourth graders at MI Darul Ma'arif Numbay. In addition to stimulating students' interest in various possible career choices, it is believed that a solid understanding of diverse professions will help them identify and appreciate different roles in society. This study used a classroom action design combined with qualitative methodology. Thirty fourth-grade students participated in this study and were supervised while they were learning. Observations, interviews, and questionnaires intended to measure students' understanding before and after the role-playing approach were practiced were used to collect data. The findings showed that students' understanding of career information was significantly better with the use of the role-playing method. Before implementing this strategy, the average student understanding score was 65%; after the role-playing exercise, the figure increased to 85%. Furthermore, as seen from their interactions with each other and their participation in debates, students showed high interest and active involvement in the learning process. However, the results of this study offer recommendations for teachers to use role-playing as an effective teaching strategy and contribute positively to the creation of fresh and innovative social studies teaching methods. In addition to encouraging further research on learning tactics that can improve students' understanding in other subjects, this research is expected to serve as a reference for the creation of more dynamic and engaging teaching techniques.